HIV care cascade for women living with HIV in the Greater Toronto Area versus the rest of Ontario and Canada. (January 2023) - Medeiros, Priscilla; Warren, Laura; Kazemi, Mina; Massaquoi, Notisha; Smith, Stephanie; Tharao, Wangari; Serghides, Lena; Logie, Carmen H; Kroch, Abigail; Burchell, Ann N; de Pokomandy, Alexandra; Kaida, Angela; et al.
Background: The Greater Toronto Area (GTA) is home to 39% of Canada's population living with HIV. To identify gaps in access and engagement in care and treatment, we assessed the care cascade of women living with HIV (WLWH) in the GTA versus the rest of Ontario and Canada (in this case: Quebec and British Columbia). Methods: We analyzed 2013–2015 self-reported baseline data from the Canadian HIV Women's Sexual and Reproductive Health Cohort Study for six care cascade stages: linked to care, retained in care, initiated antiretroviral therapy (ART), currently on ART, ART adherence (≥90%), and undetectable (<50 copies/mL). Multivariable logistic regression was used to reveal associations with being undetectable. Results: Comparing the GTA to the rest of Ontario and Canada, respectively: 96%, 98%, 100% were linked to care; 92%, 94%, 98% retained in care; 72%, 89%, 96% initiated ART; 67%, 81%, 90% were currently using ART; 53%, 66%, 77% were adherent; 59%, 69%, 81% were undetectable. Factors associated with viral suppression in the multivariable model included: living outside of the GTA (Ontario: aOR = 1.72, 95% CI: 1.09–2.72; Canada: aOR = 2.42, 95% CI: 1.62–3.62), non-Canadian citizenship (landed immigrant/permanent resident: aOR = 3.23, 95% CI: 1.66–6.26; refugee/protected person/other status: aOR = 4.77, 95% CI: 1.96–11.64), completed high school (aOR = 1.77, 95% CI: 1.15–2.73), stable housing (aOR = 2.13, 95% CI: 1.33–3.39), income of ≥20, 000 (aOR = 1.52, 95% CI: 1.00–2.31), HIV diagnosis <6 years (6–14 years: aOR = 1.75, 95% CI: 1.16–2.63; >14 years: aOR = 1.87, 95% CI: 1.19–2.96), and higher resilience (aOR = 1.02, 95% CI: 1.00–1.04). Conclusion: WLWH living in the GTA had lower rates of viral suppression compared to the rest of Ontario and Canada even after adjustment of age, ethnicity, and HIV diagnosis duration. High-impact programming for WLWH in the GTA to improve HIV outcomes are greatly needed.